TRANSFORMASI SISTEM INFORMASI AKUNTANSI ARUS KAS DENGAN MENGGUNAKAN VISUAL STUDIO DAN MYSQL PADA CV. MUTIARA SEJAHTERA - Bustamin, Syamsumar; Hadi, Abri (Universitas Methodist Indonesia, 2023)
This research focuses on the importance of accounting information systems in the retail business, with a case study on CV. Mutiara Sejahtera. We use qualitative methods and development cycle systems to understand the needs and overcome the constraints in managing a financial company. With business growth, managing data receipts, transactions, and expenses becomes complicated. A more integrated accounting information system is implemented to record and process data more efficiently. This helps reduce human error and provides better financial reports. The results of the implementation of this new system provide benefits for CV. Mutiara Sejahtera. Finances are managed more efficiently, and more accurate reports help decision-making. Thus, the implementation of an integrated accounting information system has the potential to support business growth and build operational transparency.